Evaluation of the iPad as a low vision aid for improving reading ability - Haji SA (Dove Medical Press, 2014)
Shamim A Haji, Kumar Sambhav, Sandeep Grover, Kakarla V Chalam Department of Ophthalmology, University of Florida College of Medicine, Jacksonville, FL, USA Purpose: To evaluate the effect of the iPad as a low vision aid in improving the reading ability of low vision patients (LVPs). Methods: In this study, 228 consecutive patients that came for their routine eye care examination at the University of Florida, Jacksonville eye clinic, were enrolled. Patients met inclusion criteria if they had best-corrected visual acuity (BCVA) of 20/100 or worse in the best corrected eye and were willing to participate in the study. The patient’s reading ability was assessed both with the patient’s own spectacles and an iPad. Patients were encouraged to enlarge the reading material as well as change the contrast until they could read comfortably. The number of patients able to read the text comfortably was recorded. Results: Out of the total 228 participants who qualified, 103 (45%) were male and 125 (55%) were female. Only 22% could read standard newsprint-sized text (N8) without the help of an iPad. With the help of an iPad, 94% participants with impaired vision were able to read standard newsprint-sized text (N8) or smaller text (P<0.01). Conclusion: The iPad, a new portable electronic media device, can be adapted by LVPs to improve their reading ability. Keywords: low vision devices, low vision patient, LVP, iPad